Numerical Analysis of Ion Flow in One-Bipole HVDC Transmission Line Using Revised Charge Injection Methods - Minhee Kim; Se-Hee Lee (IEEE Access, 2024)
In the evolving field of electric power transmission networks, high-voltage direct current (HVDC) transmission has garnered attention for its efficacy in long-distance power delivery. However, HVDC systems are susceptible to corona discharges, which generate ions that disrupt the electric field distribution and pose safety concerns. To address these challenges, this study introduces new calculation techniques for predicting the electric field and ion current density around HVDC transmission lines using the finite-element method. The onset fields for the corona discharge were established at 14 and 13 kV/cm for positive and negative ions, respectively. Three novel techniques—average (A), cosine (C), and average–cosine combination (AC)—were introduced for continuous charge distribution. Additionally, an enhancement factor $β$ was incorporated to reflect the various climatic conditions, enhancing the model’s adaptability. This approach streamlines the analysis by reducing the reliance on complex parameters such as conductor roughness coefficient and climate constants. The techniques were validated across four different bundle configurations of transmission lines, with the AC technique demonstrating superior accuracy in predicting the electric field and ion current density, affirming its robustness in diverse scenarios, including under wind conditions. This research marks a significant advancement in modeling electrical discharge phenomena in HVDC environments, providing a simplified yet precise tool for ensuring electrical safety.